2D Magnetic Mesocrystals for Bit Patterned Media. Issue 21 (6th August 2018) - Guo, Shanshan; Xu, Feng; Wang, Baomin; Wang, Ning; Yang, Huali; Dhanapal, Pravarthana; Xue, Fei; Wang, Junling; Li, Run‐Wei
Abstract: Bit patterned media exhibits great potential in satisfying the increasing demand for higher information storage density, but the present media fabrication technique is complicated. Here, a 2D magnetic mesocrystal with monodisperse CoFe2 O4 (CFO) nanocrystals is fabricated through a combination of nanoseeds layer growth and oxides self‐assembly method. The monodisperse CFO nanomagnets protrude from the substrate surface with perfect crystal facets, specific crystallographic orientation, and are fully relaxed. Systematic magnetic characterizations, such as dynamic cantilever magnetometry for single CFO nanocrystal, magnetic force microscopy, and superconducting quantum interference device magnetometry for large area, reveal the novel tilted magnetic anisotropy and the switchable single domain state. This work provides a new way to fabricate bit patterned media with controlled material structure simply by a nanoseeds‐mediated self‐assembly method. Abstract : A 2D magnetic CoFe2 O4 (CFO) mesocrystal is fabricated by a nanoseeds‐mediated self‐assembly method. The monodisperse CFO nanomagnets protrude from the substrate surface with perfect crystal facets and specific crystallographic orientation. Systematic magnetic characterizations, such as dynamic cantilever magnetometry for single CFO nanomagnet, magnetic force microscopy, and superconducting quantum interference device for large area, reveal the novel tilted magnetic anisotropy and the switchable single‐domain state.